STUDI TENTANG KESEHATAN MENTAL PESERTA DIDIK KELAS VII SEKOLAH MENENGAH PERTAMA NEGERI 3 SUNGAI RAYA - Mosa, Efrilly; Yuline, Yuline; Wicaksono, Luhur (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractÂ This study aims to obtain an overview to analyze how the mental health of learners in State Junior High School 3 Sungai Raya, and how the mental health characteristics of learners, and how factors that cause mental health of learners, and how the efforts of teachers Guidance and Counseling in improving the mental health of learners. The method used in this research is the descriptive method in the form of survey study that is the procedure with the problems investigated by describing or describing the mental health of the students of class VII in State Junior High School 3 Sungai Raya, and explained descriptively. Data collection in this study using questionnaire. Based on the results of mental health data analysis, students of Grade VII of Junior High School 3 Sungai Raya achieved actual score of 7850 and an ideal score of 9720 with 81% percentage of "Good" category. Which means showing that the mental health of students VII grade of Junior High School Negeri 3 Sungai Raya have good mental health.Keywords: Mental Health, Learners